Simultaneous Detection of Bisphenol A and Bisphenol S Migration in Food-Contact Plastics Based on a Dual-ligand Metal-organic Framework - Qian LIN; Genling LIN; Lili DAI; Dihui HUANG; Xiaozhou HUANG (Shipin gongye ke-ji)
This study reported the synthesis of a novel composite material, Cu-BTC-HHTP/MWCNT. The material was synthesized via a solvothermal method using copper nitrate (Cu(NO3)2), 1,3,5-benzenetricarboxylic acid (H3BTC), and 2,3,6,7,10,11-hexahydroxytriphenylene (HHTP) as dual-ligand metal-organic frameworks, which were incorporated into multi-walled carbon nanotubes (MWCNT) to create a composite with superior electrical conductivity. The material was characterized by scanning electron microscopy, X-ray diffraction, and Fourier transform infrared spectroscopy. A glassy carbon electrode (GCE) was modified with the Cu-BTC-HHTP/MWCNT composite to develop an electrochemical sensor, referred to as Cu-BTC-HHTP/MWCNT/GCE. Cyclic voltammetry was used to optimize the construction conditions of the sensor, including the choice of electrolyte, system pH, accumulation potential, and accumulation time. Under optimal conditions, the sensor exhibited a linear relationship between peak current response and bisphenol A (BPA) and bisphenol S (BPS) concentrations in the range of 5 to 400 μmol/L, with coefficient of determination (R2) of 0.997 for BPA and 0.998 for BPS. The detection limits were 76.4 nmol/L for BPA and 18.5 nmol/L for BPS. In real sample testing, the method demonstrated excellent recovery rates, ranging from 96.63% to 103.69% for BPA and from 98.29% to 101.18% for BPS. These results indicate that the Cu-BTC-HHTP/MWCNT/GCE sensor provides a robust platform for the detection of BPA and BPS migration from food-contact materials, providing a reliable analytical tool for investigating the migration of these contaminants.